Case Report: Diagnosis of Klebsiella pneumoniae Invasive Liver Abscess Syndrome With Purulent Meningitis in a Patient From Pathogen to Lesions - Zeng, Sheng; Yan, Wei-qian; Wu, Xiao-mei; Zhang, Hai-nan (Frontiers in Medicine, 2021)
As a determinant human nosocomial pathogen, Klebsiella pneumoniae is known to cause rare K. pneumoniae liver abscess syndrome (KLAS) which was common in Asian in early stage and developed as a global disease now. Patients with KLAS who have septic metastatic ocular or central nervous system (CNS) lesions associated with high morbidity and mortality. Until now, only few adult community-acquired K. pneumoniae meningitis have been recorded and could hardly survive in this disease. In this paper, we reported a case of KLAS presenting purulent meningitis as disease onset. While negative results were obtained in bacterial culture of CSF, blood or liver pus, metagenomic next-generation sequencing (mNGS) which was synchronously performed demonstrated Klebsiella pneumoniae as the pathogenic microorganism. The patient who was healed in the end benefited from rapid pathogen diagnosis, early percutaneous drainage of the abscess and prompt appropriate antibiotic administration. Our case highlights the importance of clinician awareness of early pathogen diagnosis by mNGS of this disease. Moreover, it suggested the potential of diagnosis of severe infectious diseases from pathogen to lesions.